Knowledge and Perceptions of, and Attitudes to, Bats by People Living around Arabuko-Sokoke Forest, Malindi-Kenya. (4th March 2018) - Musila, Simon; Prokop, Pavol; Gichuki, Nathan
ABSTRACT: Bat populations continue to decline worldwide because of myriad human activities. To enhance bat conservation, human behavior needs to change. Such change can occur, in part, through an understanding of what motivates human actions toward bats. We used a Bat Attitude Questionnaire (BAQ) to investigate attitudes toward bats in people ( n = 394) living around Arabuko-Sokoke Forest (ASF), Kenya. Belief in myths seemed to prevail among those surveyed and that these myths were significantly associated with low tolerance of bats (ordinal regression, p < 0.05). Older and more educated people reported more positive attitudes toward bats than others. Multiple linear regression revealed that females showed more negative attitudes toward, and more belief in, myths about bats than males (both p < 0.01). Ordinal regression showed that hostile behavior toward bats was more common among males ( p < 0.001). Nearly one-third of the respondents reported actively killing bats or destroying bat roosts. A similar proportion did not see any benefits of bats to humans, while the majority of respondents associated bats with the destruction of farmers' fruits. To address prevailing negative attitudes about bats, we recommend conducting evening school-based bat study tours, specifically targeting youths in schools around the forest, to examine whether physical contacts with bats would help positively influence human attitudes toward bats. Additionally, since mango ( Mangifera indica ) farming is an important source of income to people around ASF, an assessment of the quantity of mangoes destroyed by bats would be important to determine whether there is a need for controlling bat access to crops through appropriate schemes.